Loyalitas Pelanggan Di Pasar Gading Kios 45 - Nurchasanah, Vindawati, Susatyo Yuwono ,S. Psi., M. Si (2015)
The purpose of this research is to know the dynamic loyalty of the Gading Market customers in Kios 45. The number of the informant is 10 people who always shop in Kios 45. The election of the informant is based on the purposive sampling. There are three divisions of the informant. First, three informants are people who go shopping for 10-15 years.Second, four informants are people who go shoping for 14-20 years. Third, the informants are people who go shopping for more than 20 years. The result of this research is the customers of Kios 45 is concluded as loyal customers. This is shown from the customer who always buy product in big amount. They never bargained products. And they used to recommend Kios 45 to others and show the demerits of other stores. The customers of Kios 45 are customers who have high loyalty. According to loyalty degree, ninr informants go shopping 6-7 days which is called as premium loyalty. And informant BG who show the hidden loyalty because they only go shopping 3 days per week. Every customer has different reason to go shopping at Kios 45. Aj said, he buy products in Kios 45 because of the exact scales. SL said in other store the scales is not exact, but in Kios 45 it's always exact. On the other hand, informant BN and YN said that it feels comfort to share story with the seller. This can't be happened in other store. Informant SP and SH said that the price in Kios 45 follow the price market. If the price is high, so the price of the products will be high. When the price is low, the price of the product will also be low. Informant BG said that he knows the owner of Kios 45 from one community. Informant AT said that he never feel awkward when he go shopping in Kios 45. He never feel the same in other stores. SR said the prices in Kios 45 is very low, so we can sell the product again. Besides, we don't need transport when we go shopping. Informant TK has a reason that she becomes the customer of kios 45 because of the good quality of the product.